ANALISIS PREFERENSI KONSUMEN TERHADAP BUAH JERUK LOKAL DAN BUAH JERUK (SUNKIS) IMPOR KOTA PALU - Isen, Isen; Lamusa, Arifuddin; Effendy, Effendy (AGROTEKBIS, 2016)
This study aims to determine the attributes of local and imported citrus fruits mostly considered and preferred in Palu. The number of Respondents was 60 people determined using an incidental sampling technique. Data were analyzed using chi square and Fishbein multiattribute analyses. The result of the research showed that the number of respondents aged between 19 â 27 years who bought both local and imported citrus is eight respondents while whose aged between 28 â 36 years is 21 respondents (53%). The respondents whose age > 36 years (18 people, 35%) prefer to buy imported citrus. Based on the results of chi square analysis, there are differences in consumer preferences on all attributes of local and imported citrus except on the fruit color of the imported fruits. The results of the Fishbein multiattribute analysis indicate that the attributes of the local fruits mostly considered by the respondents are flavor, price, size and color whereas that of the imported fruits are flavor, color, size and price. Â Key Words: Consumer preferences, fruit attributes, local citrus, and imported citrus.